2014
DOI: 10.1016/j.knee.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic washout of the knee: A procedure in decline

Abstract: Background: Osteoarthritis (OA) of the knee is a chronic, progressive condition which often requires

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…These findings are consistent with ours, as the data were extracted from a National Patient Register in a Scandinavian country similar to those in the current bi-national study. Moreover, Lazic et al (2014) reported a similar increase in meniscus surgery for patients over 65 years of age in the UK between 2000 and 2012. In the present study, the incidence of surgery for degenerative meniscal tears increased in Finland from 1997 to 2007, but not in Sweden.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These findings are consistent with ours, as the data were extracted from a National Patient Register in a Scandinavian country similar to those in the current bi-national study. Moreover, Lazic et al (2014) reported a similar increase in meniscus surgery for patients over 65 years of age in the UK between 2000 and 2012. In the present study, the incidence of surgery for degenerative meniscal tears increased in Finland from 1997 to 2007, but not in Sweden.…”
Section: Discussionmentioning
confidence: 79%
“…In the UK, the incidence of arthroscopic meniscal resections more than doubled from 2000 to 2012 in patients over 60 years of age (Lazic et al 2014). Similarly, in Denmark the number of meniscal procedures in patients aged 35 years or more increased during the period 2000–2011 (Thorlund et al 2014).…”
mentioning
confidence: 99%
“…8 The data were presented for the four arthroscopic codes separately. We re-evaluated the data presented and found that although rates of arthroscopic irrigations had fallen, this reduction was dwarfed by a large increase in the number of arthroscopic meniscal resections, resulting in an overall increase in procedures.…”
Section: Rates Of Arthroscopy In People Over 60mentioning
confidence: 99%
“…A cynic may suggest that in countries such as Australia and the USA, where many surgeons have a strong personal financial incentive to operate, non-medical decisions may be acting as a barrier to reducing knee arthroscopy. However, in countries where the financial incentive to surgeons is less, recent reports have yet shown an increase in knee arthroscopies, such as in Denmark,8 and a marginal drop only in the UK 9. In other words, it is not just the profit motive of surgeons leading to the high rate of this operation.…”
Section: Change In Knee Arthroscopy Rates Subsequent To New Evidencementioning
confidence: 99%